Study protocol: a prospective single-center study for non-invasive biomonitoring of renal complications in cancer patients treated with immune checkpoint inhibitors - Baier, Eva; Korsten, Peter; Strauß, Arne; Thoms, Kai-Martin; Overbeck, Tobias; Ströbel, Philipp; Tampe, Björn (Frontiers in Immunology, 2023)
Background: The advent of immune checkpoint inhibitors (ICIs) has powerfully broadened the scope of treatment options for malignancies with an ongoing increase of indications, but immune-related adverse events (irAEs) represent a serious threat to treatment success. Agents directed against programmed cell death protein 1 (PD-1) or its ligand 1 (PD-L1) are known to cause renal complications with an incidence of 3%. In contrast, subclinical renal involvement is estimated to be much higher, up to 29%. We recently reported about urinary flow cytometry-based detection of urinary PD-L1-positive (PD-L1+) kidney cells correlating with tubular PD-L1-positivity that reflected susceptibility to develop ICI-related nephrotoxicity as an irAE attending ICI treatment. Therefore, we designed a study protocol to evaluate urinary detection of PD-L1+ kidney cells as a tool for non-invasive biomonitoring of renal complications in cancer patients treated with ICIs. Methods: A prospective, controlled, non-interventional, longitudinal, single-center observational study will be conducted at the Department of Nephrology and Rheumatology of the University Medical Center Göttingen, Germany. We intend to enroll approximately 200 patients treated with immunotherapy from the Departments of Urology, Dermatology, and Hematology and Medical Oncology of the University Medical Center Göttingen, Germany. First, we will assess clinical, laboratory, histopathological, and urinary parameters in addition to urinary cell collection. Then, we will perform a correlative analysis between urinary flow cytometry of different PD-L1+ cell of renal origin with the onset of ICI-related nephrotoxicity. Discussion: Because of growing ICI-treatment applicability with an expectable incidence of renal complications, providing cost-efficient and easily performable diagnostic tools for treatment-attendant and non-invasive biomonitoring becomes vital to improve both renal and overall survival rates in cancer patients receiving immunotherapy. Trial registration: https://www.drks.de, DRKS-ID: DRKS00030999